Urban and Regional Dynamics in Poland - Deichmann, Uwe (World Bank, Washington, DC, 2015)
In this exploration of urban and regional dynamics in Poland after the transition, the authors find that the degree of urbanization, and primacy remains low in Poland. The largest cities are not growing at the rate that would be expected if post-transition adjustments were operating freely. As a result, Poland is not fully realizing external economies from urban agglomeration. Internal migration decreased significantly in the 1990s, with rural-to-urban migration declining dramatically. Current population levels everywhere seem frozen at a degree of urbanization that is low by international standards. Migration levels do not respond to unemployment differentials, perhaps because Poland's continuing housing shortage, deters migration. Housing construction, which was already low, fell by half in the 1990s, and has only recently begun a slight recovery. A significant number of mostly young, and educated temporary migrants leave Poland annually, many to find employment abroad. This may reduce pressure on the Polish labor market, but also keeps dynamic actors our of the domestic labor force, reducing growth in urban businesses and industry. Employment in manufacturing and agriculture is relatively concentrated, but specialization seems to have declined in recent years, perhaps reflecting barriers to labor mobility - which could limit growth. That employment in the manufacturing sector is quite concentrated, is to be expected in a formerly planned economy. But employment in the service sector, is also quite concentrated. A geographic divergence of service activities is not explained by dominant growth in specialized financial, and business services in the capital alone. Poland's policymakers should find a way to provide housing, thereby reducing barriers to labor mobility, and growth.